Art Of Folklore, This Is Humanity's Childhood Song - Nargiza Rahmatullaeva (Genius Journals, 2024)
The article describes the search for folklore, the hard work of folklorists, the technology of recording epics and preparing them for publication
Keywords: Folklore; epic; Alpomish; Badash